2022
DOI: 10.1111/jcmm.17402
|View full text |Cite
|
Sign up to set email alerts
|

Microbial gut evaluation in an angolan paediatric population with sickle cell disease

Abstract: Sickle cell disease (SCD) is a relatively common genetic disease, being a growing health problem in many parts of sub-Saharan Africa, and about 300,000 affected children are born with this condition every year. 1 In Africa, the mortality rate among SCD children under the age of 5 years can be as high as 90%. 2 This Mendelian disease results from a single-nucleotide polymorphism (rs334), which changes the position 17 of HBB gene from thymine to adenine, resulting in the replacement of glutamic acid to valine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…31 Rhodospirillales sp., also less abundant in TOW mice, had low abundance in patients with SCD. 29 We found higher abundances of Lactobacillus sp., Monoglobus sp., Odoribacter sp., Lachnoclostridium sp., Muribaculaceae, Clostridia_vadinBB60_group , Oscillibacter sp., and Muribaculum sp. in TOW mice.…”
Section: Discussionmentioning
confidence: 67%
“…31 Rhodospirillales sp., also less abundant in TOW mice, had low abundance in patients with SCD. 29 We found higher abundances of Lactobacillus sp., Monoglobus sp., Odoribacter sp., Lachnoclostridium sp., Muribaculaceae, Clostridia_vadinBB60_group , Oscillibacter sp., and Muribaculum sp. in TOW mice.…”
Section: Discussionmentioning
confidence: 67%
“…A reduced nutritional intake is known to shift the gut microbiome. For example, iron deficiency results in a reduction of Bifidob acterium, [210][211][212] Bacteroides, 213 and Faecalibacterium 214 and causes a shift in SCFA 215 as well as siderophore-production, 213 while an increase of the Actinobacteria phylum [216][217][218] is reported. Vitamin A deficiency rather promotes Enterococcus in children with diarrhea, 219 while Bacteroides and Bifidobacterium are decreased.…”
Section: Inflammationmentioning
confidence: 99%
“…26 They observed differences at the microbial composition when they modeled the top 15 bacterial genera, but did not find differences at the phylum level or in diversity. Delgadinho and colleagues showed that Angolan children (3-14 years) 40 had higher Actinobacteria phylum, and Clostridium were more prevalent in the SCA population. In our study, the gut microbial diversity was similar between the HbSC (less severe form of sickle cell disease) and HC, but the alpha diversity was different between the SCA (HbSS) cohort and HC, although the difference seen did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%